Single-cell spatial atlas of smoking-induced changes in human gingival tissues - Yong Zhang; Zongshan Shen; Jiayu Yang; Junxian Ren; Chi Zhang; Lingping Tan; Li Gao; Chuanjiang Zhao (International Journal of Oral Science)
Abstract Smoking is a well-established risk factor for periodontitis, yet the precise mechanisms by which smoking contributes to periodontal disease remain poorly understood. Recent advances in spatial transcriptomics have enabled a deeper exploration of the periodontal tissue microenvironment at single-cell resolution, offering new opportunities to investigate these mechanisms. In this study, we utilized Visium HD single-cell spatial transcriptomics to profile gingival tissues from 12 individuals, including those with periodontitis, those with smoking-associated periodontitis, and healthy controls. Our analysis revealed that smoking disrupts the epithelial barrier integrity, induces fibroblast alterations, and dysregulates fibroblast–epithelial cell communication, thereby exacerbating periodontitis. The spatial analysis showed that endothelial cells and macrophages are in close proximity and interact, which further promotes the progression of smoking-induced periodontal disease. Importantly, we found that targeting the endothelial CXCL12 signalling pathway in smoking-associated periodontitis reduced the proinflammatory macrophage phenotype, alleviated epithelial inflammation, and reduced alveolar bone resorption. These findings provide novel insights into the pathogenesis of smoking-associated periodontitis and highlight the potential of targeting the endothelial–macrophage interaction as a therapeutic strategy. Furthermore, this study establishes an essential information resource for investigating the effects of smoking on periodontitis, providing a foundation for future research and therapeutic development for this prevalent and debilitating disease.